1999
DOI: 10.1108/eb022818
|View full text |Cite
|
Sign up to set email alerts
|

Complaint Handling on the Shop Floor: Cooperative Relationships and Open‐minded Strategies

Abstract: Managing conflicts between employees and supervisors is a critical issue in maintaining productive labor‐management relations. This study uses the theory of cooperation and competition to specify the nature of the relationship and the flexible strategies that facilitate mutually beneficial solutions to employee complaints. Results based on interviews of supervisors and union employees in a remote site in British Columbia support the hypotheses that cooperative, compared to competitive and independent, goals pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 73 publications
1
38
0
5
Order By: Relevance
“…For example, management and union representatives with cooperative goals expressed their opposing views directly to each other, listened open-mindedly, conveyed an intent to work for mutual benefit, and combined their ideas. With this kind of discussion, they developed creative, quality solutions and used their resources efficiently Tjosvold, Morishima, & Belsheim, 1999). They resolved their grievances with positive feelings, satisfied both union and management, and improved procedures that would help them resolve future grievances.…”
Section: Managing Interest and Emotional Conflictmentioning
confidence: 93%
“…For example, management and union representatives with cooperative goals expressed their opposing views directly to each other, listened open-mindedly, conveyed an intent to work for mutual benefit, and combined their ideas. With this kind of discussion, they developed creative, quality solutions and used their resources efficiently Tjosvold, Morishima, & Belsheim, 1999). They resolved their grievances with positive feelings, satisfied both union and management, and improved procedures that would help them resolve future grievances.…”
Section: Managing Interest and Emotional Conflictmentioning
confidence: 93%
“…A major trigger to such engagement is perceptions of goal cooperation rather than goal competition (Tjosvold et al, 1999). Goals are cooperative when the parties perceive that the achievement of each of their goals promotes the achievement of the other party's; they are competitive when the parties believe that the other's success will inhibit their own.…”
Section: Research On Complaint Interactionsmentioning
confidence: 99%
“…It is also known as a competing, controlling, contending, win-lose, or zero-sum style (Rahim, 2001;Rahim et al, 2000). Studies that have extended the cooperativecompetitive conflict management typology to organizational settings (e.g., Kuhn & Poole, 2000;Tjosvold, 1999;Tjosvold et al, 2005;Tjosvold, Morishoma, & Belsheim, 1999) have demonstrated that conflict dynamics and team outcomes are greatly affected by whether team members emphasize a cooperative or a competitive conflict-management approach. According to Deutsch's (1973Deutsch's ( , 1980 theory of cooperation and competition, team members may choose to emphasize their common goals.…”
Section: Introductionmentioning
confidence: 99%